The influence of consequentiality on perceptions of crime seriousness - Casey, Sinead (Legal and criminological psychology, 1999)
Objective. To investigate whether some individuals take into account the consequences of an offence as well as the perpetrator's intention when evaluating the seriousness of that offence. Method. A sample of respondents (N = 133) was asked to rate the seriousness of two sets of offences, the sets differing not in the acts described but in the consequences of each act. A group of ratio scores was devised on the basis of the relationship between the ratings of two criminal acts differing only in their consequences. Results. Respondents did not show a uniform response to the change in outcome. One factor was extracted from the ratio scores and proved significant in explaining the variance of seriousness perceptions towards two further offence vignettes. Conclusions. The intentionality of the offender appears to be important for all individuals in rating seriousness while only some are also influenced by the outcome of the act. Consensus about offence seriousness is achieved despite the use of very different rules of evaluation.